2019
DOI: 10.1080/03079457.2019.1620915
|View full text |Cite
|
Sign up to set email alerts
|

A combined retrospective, prospective and experimental study ofOrnithobacterium rhinotrachealeinfection in chickens

Abstract: The aim of this study was to examine the histopathological and immunohistochemical changes caused by natural and experimentally-induced Ornithobacterium rhinotracheale infection in the respiratory system of chickens. To this end, three different studies were carried out. The first was a retrospective study of 82 field cases with respiratory disorders compatible with O. rhinotracheale infection. The bacterium was immunohistochemically detected in the lungs in 48 of 82 field cases, and 50 β-haemolytic (BH) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…ORTs of 21 were isolated from 65 sampled birds (Umali et al., 2018 ). Churria et al., In Argentina, showed that out of 82 swab samples from broiler trachea and lung tissue, 50 were identified as ORT‐positive samples (Gornatti‐Churria et al., 2019 ; Umali et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…ORTs of 21 were isolated from 65 sampled birds (Umali et al., 2018 ). Churria et al., In Argentina, showed that out of 82 swab samples from broiler trachea and lung tissue, 50 were identified as ORT‐positive samples (Gornatti‐Churria et al., 2019 ; Umali et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to the rapid and heavy growth of other bacteria colonies, which led to their coverage ORT, in addition to the small size of the ORT colonies compared to other bacterial strains, difficulties have been observed [40]. Due to these causes, an increased rate in the complexity of isolating ORTs was observed [16,41], which was also dependent on the high resistance of bacteria in samples similar to gentamicin at a concentration of 10 µg/mL. These observed features served as an obstacle to ORT isolation.…”
Section: Detection Of Ort Using the Indirect Methodsmentioning
confidence: 99%